The construction of modalities in Indonesian and English folktales - Surjowati, Ribut; Wirawati, Bekti; Kusnowati, Siti; Wijaya, Wiemphy; Syahputra, Bintang Yusma Dian (LingTera, 2024)
This paper aims to describe the types of modality expressions in English and Indonesian folktales and to examine the extent to which these two groups of writers express modality differently. This study was conducted as descriptive qualitative research, focusing on the use of modalities in Indonesian and English folktales. A total of 30 folktales were collected from the United States, Britain, and Indonesia as the data sources. The data were analyzed based on the theories of Nuyts (2002) and Bybee (1994). The results show that native English writers tend to express deontic modality primarily through modal auxiliaries such as shall, should, can, could, must, and may. However, epistemic meanings are conveyed not only through modal auxiliaries but also through adjectives, adverbs, and lexical verbs, with lexical verbs being the most frequently used. In contrast, non-native writers used fewer varieties of modality expressions, including modal auxiliaries, adjectives, adverbs, lexical verbs, and multi-word units, often relying on the same types of expressions across the folktales. Unlike deontic modality, the folktales are rich in epistemic modality, as the writers used a wider range of expressions to convey these meanings.